Assessment of Association between Natriuretic Peptides (MR-pro-ANP and NT-pro-BNP) and Cardiovascular Risk in Patients with Type II Diabetes: A Prospective Observational Study - Singh, Daniel Sundar; Pithadia, Anand; Lavanya (International Journal of Pharmaceutical Investigation, 2025)
Background Cardiovascular disease is the major cause of morbidity and mortality in individuals with T2DM. Although many promising cardiac markers have been identified, a single Natriuretic peptide biomarker is unlikely to aid T2DM patients with CVDs. Hence, we attempted to provide a brief insight into the association between natriuretic peptides and Cardiovascular risk in T2DM by using the UKPDS-10 years risk stratification tool. Objectives The study aimed to assess the association between natriuretic peptides (MR- pro-ANP and NT Pro-BNP) and CVD in T2DM patients. Materials and Methods A prospective observational study was conducted in a tertiary care hospital, with a sample size of 74. This study was carried out for 6 months. Based on the inclusion and exclusion criteria, patients has been enrolled in the study and the data were collected. Cardiovascular risk assessments 10 years were performed by utilizing the UK Prospective Diabetes Study (UKPDS) tool. Results Out of 74 patients in our study, we found a significant correlation between UKPDS risk score, CVD, and natriuretic peptides in T2DM. The following results were found in our study: 1) Association between HbA1c vs. UKPDS 10-year cardiac risk score (p value=0.026) 2) Association between HbA1c and NT-Pro BNP (p value=0.017) 3) Association between HbA1c and MR-Pro ANP (p value=0.002) 4) Association between UKPDS 10-year cardiac risk score and NT-Pro BNP (p value=0.000) 5) Association between age and NT Pro BNP (p value=0.044) 6) Association between Age vs. MR-Pro ANP (p value=0.033) 8) Association between UKPDS 10-year risk score and CVD (p value=0.038). Conclusion In conclusion the data shows that there is a significant correlation between Natriuretic peptides and CVD hence, higher Natriuretic peptide levels in T2DM are directly associated with cardiovascular risk.
Keywords: Cardiovascular risk; Type-2 Diabetes Mellitus; Natriuretic Peptides (NT-Pro BNP; MR-Pro ANP); UK Prospective Diabetes Study (UKPDS)